TMIC-05. SINGLE-CELL MULTI-OMIC ANALYSIS OF SPORADIC VESTIBULAR SCHWANNOMAS REVEALS SCHWANN CELLS WITH AN INJURY PHENOTYPE AND AN ASSOCIATION BETWEEN TUMOR SIZE AND MACROPHAGE INFILTRATE. (14th November 2022) - Patel, Bhuvic; Barrett, Thomas; Pugazenthi, Sangami; Khan, Saad; Yim, Aldrin; Buchman, Craig; Patel, Akash; Petti, Allegra; Puram, Sid; Kim, Albert
Abstract: Vestibular schwannomas (VS) comprise 8% of primary brain tumors, with rising prevalence due to increased detection by imaging. How intertumoral heterogeneity and differences within the tumor microenvironment (TME) contribute to the pathogenesis of VS remains poorly understood. We performed single-cell RNA sequencing (scRNA-seq) on 15 sporadic VS with paired single-nucleus assay of transposase accessible chromatin sequencing (snATAC-seq) on 7 tumors. Dimension reduction analysis revealed diverse Schwann, immune—predominantly macrophage, and stromal cell populations. Schwann cells adopted multiple unique functional states, such as repair-like, myelinating, and hypoxia-response, reflecting undescribed intratumoral heterogeneity within VS-associated Schwann cells. Remarkably, VS-associated Schwann cells were found to be phenotypically similar to Schwann cells in the setting of peripheral nerve injury, which is robustly associated with macrophage recruitment. Indeed, using our scRNA-seq atlas to perform deconvolution analysis of a broader cohort of VS, including newly sequenced (n = 22) and published bulk RNA-sequencing datasets (n = 153), we found variation in proportion of immune cells was strongly correlated with the proportion of macrophage infiltrate (R, 2 = 0.86, p < 0.001). Furthermore, we found that macrophage/monocyte lineage cells represent a disproportionately large number of cycling cells in the VS TME, a finding corroborated by immunohistochemistry. Clinically, tumors with high macrophage infiltrate were associated with larger tumor size (Fisher's exact test p = 0.007). Together, these findings suggest macrophages play an important role in VS pathogenesis. We therefore sought to characterize potential cell-to-cell interactions between Schwann cells and macrophages in our scRNA-seq atlas. Ligand-receptor analysis revealed several cytokines expressed by Schwann cells with cognate receptors expressed by macrophages, including MIF, SPP1, MDK, SEMA3C and IL34, which may be responsible for recruiting macrophages. In summary, we describe previously uncharacterized cellular diversity within VS, highlight an association between macrophage infiltration and clinical phenotypes, and identify potential therapeutic targets for VS treatment.